Peran Faktor Peternak dan Inseminator terhadap Keberhasilan Inseminasi Buatan pada Sapi Potong di Kecamatan Kota Bangun - Fikri Ardhani; Lukman Lukman Lukman; Firda Juita (Universitas Mulawarman, 2020)
Some of the factors that influence the success of artificial insemination are livestock, semen quality and human (breeders and inseminator). The research aim is to characterize on human factors including the characteristics, knowledge, and skills and its role affecting the success of artificial insemination in the Kota Bangun District. This research was conducted in Kota Bangun District, by interview method in the form of questionnaire to 54 breeders and 3 inseminators. The data were analyzed using descriptive statistics, including; frequency distribution, percentage and Guttman measurements. This research shows that breeder characteristics; age, education and breeding experience, as well as characteristics of inseminator officers; age, education, training and AI experience are high and good in supporting knowledge and skills. The knowledge level of breeders and inseminators about reproduction and AI technology are high so it can affect the success of AI. Farmer’s skill; time of observation lust, the right time for AI and pregnancy detection are high, as wel as inseminator officer skills; recognize the signs of lust, the right time for AI and pregnancy detection are high, so it can affect the success of AI. The success of AI with S/C value of 1,44 and CR of 76% are good and ideal. Thus, the factor of breeder and inseminator officer is high with percentage of 78,4% in the success of artificial insemination in beef cattle in the Kota Bangun District.